Sheikh Abdul Aziz Bin Abdullah Bin Baz's Study of Hajj and Umrah Fatwas - Muhmmad Ridha DS; M. Husein Ritonga; Hadri Hasan; Badarussyamsi Badarussyamsi (CV. Rayyan Dwi Bharata, 2023)
The implementation of Hajj and Umrah According to Sheikh Abdul Aziz Bin Abdullah Bin Baz is an obligation for every free, mukallaf and capable Muslim, and only mandatory once during the hudup. Hajj must be carried out as soon as possible for the able, according to the correct opinion of the scholars. It is mandatory to carry out the Hajj for those who have debts and he is able to carry them out and is able to pay the debts. The more afdhal in carrying out the Hajj so as not to use borrowed money. It is not legal to hajj the person who leaves the prayer, as well as for the person who prays but sometimes leaves it. In general, a mujtahid in order to be able to answer all the problems of the legal case that is happening, even though the problem is not clearly found in the Qur'an and the hadith of the Prophet Muhammad saw. So, a mujtahid must also know the purpose of the law, the essence of the meaning of the law and adjust the harmony of a law with the times. In the area of fiqh, Sheikh Bin Bāz refers a lot to the school of Imam Ahmad ibn Hanbal, but Sheikh Bin Bāz stated unequivocally, that he did so not based on excessive fanaticism. If he finds a difference of opinion in the matter of fiqh, Sheikh Bin Bāz prefers to apply the method of tarjih and ijma', i.e. by choosing or or becoming a muttabi' with the rakyu of 'scholars who are stronger in opinion from the point of view of his legal istimbat based on the Qur'an and the Hadith of the Prophet Muhammad pbuh.